2008
DOI: 10.1055/s-0028-1093322
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Strength and Endurance Training on Brain-derived Neurotrophic Factor and Insulin-like Growth Factor 1 in Humans

Abstract: Blood neurotrophins like insulin-like growth factor (IGF-1) and brain-derived neurotrophic factor (BDNF) are discussed to mediate health benefits of physical activity in humans. The aim of the study was to analyze the training effects of moderate endurance training (Em) and strength training with high loads (Sh) on blood plasma concentrations of IGF-1 and BDNF in humans. Venous blood samples were obtained from 27 healthy students, randomly assigned to an Em, Sh, and a control group, before and after a 12-week … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
75
1
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(87 citation statements)
references
References 21 publications
6
75
1
5
Order By: Relevance
“…Exercise types can be broadly categorized into strength (resistance) training and aerobic training. In all previous studies on resistance training, regular training did not increase resting BDNF levels [8,15,18,25]. With regard to different periods of exercise for resistance training studies, Goekint et al [8] and Levinger et al [15] evaluated a 10-week resistance training duration, Schiffer et al [18] used a 12-week period, and Yarrow et al [25] used a 5-week duration.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise types can be broadly categorized into strength (resistance) training and aerobic training. In all previous studies on resistance training, regular training did not increase resting BDNF levels [8,15,18,25]. With regard to different periods of exercise for resistance training studies, Goekint et al [8] and Levinger et al [15] evaluated a 10-week resistance training duration, Schiffer et al [18] used a 12-week period, and Yarrow et al [25] used a 5-week duration.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Goekint et al [15] , a period of strength training in sedentary subjects did not significantly change the concentration of growth factor compared to the control group. Another study reported that the resting concentration of BDNF was not infl uenced by strength training in young subjects [14] . Maximal speed and strength are known to be important determinants of sprint performance [22,23] .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the differences in BDNF values between strength-and sprint-trained subjects may be partly due to the specifi c form of training. Heavy resistance exercise used in previous studies [14,15] was not combined with explosive types of weight training or speed concentrations in the international and the domestic sprinters were both higher than those in sedentary subjects (P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perbaikan pasien RLS pada kelompok intervensi dalam penelitian ini diperkuat dengan penjelasan bahwa aktivitas fisik berupa latihan kekuatan merupakan stimulus adaptasi fungsional dan metabolik pada neuromuskular. Latihan kekuatan memberikan hasil pada penguatan otot rangka dan peningatan kekuatan maksimal (Schiffer, Schulte, Hollmann, Bloch, & Strüder, 2009). Latihan kekuatan juga telah terbukti memengaruhi fungsi kontrol motor (Graef, Michaelsen, Dadalt, Rodrigues, & Pereira, 2014).…”
Section: Pembahasanunclassified